Chromatographic Fingerprinting of Essential Oil of Aerial Parts of Eupatorium adenophorum Spreng. Grown in Various Locations of Uttarakhand Himalaya, India. Issue 4 (4th July 2019) - Chauhan, Nirpendra; Bhandari, Ujjwal; Lohani, Hema; Haider, S. Zafar; Sah, Sunil
Abstract: The present study aims to evaluate the chemical composition of essential oils from the aerial parts of Eupatorium adenophorum Spreng. growing wild in Kumaon and Garhwal region of Uttarakhand. The composition of essential oils was investigated by GC and GC/MS analyses. The average oil yield in all the populations of E. adenophorum varied from 0.27-0.97 %. Fifty five essential oil constituents comprising monoterpenes and sesquiterpenes were identified. The GC and GC/MS analysis of the oils of the aerial parts of E. adenophorum revealed that oxygenated sesquiterpenes (25.9-41.87 %) and sesquiterpenes hydrocarbons (22.54-33.15 %) were the major class of compounds in the oils. The essential oils of E. adenophorum is rich in amorph-4-en-7-ol (12.03-19.48 %) followed by p-cymene (3.18-15.44 %), bisabolol (5.25-9.39 %), bornyl acetate (4.17-7.93 %), phellandrene (1.79-7.25 %), camphene (2.50-6.83 %), β-bisabolene (3.36-6.64 %) etc. Cluster analysis was also applied to study the chemical variability in the essential oils among populations which showed groups, although, there were no major variation seen.